2015
DOI: 10.1016/j.heares.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Auditory midbrain implant: Research and development towards a second clinical trial

Abstract: The cochlear implant is considered one of the most successful neural prostheses to date, which was made possible by visionaries who continued to develop the cochlear implant through multiple technological and clinical challenges. However, patients without a functional auditory nerve or implantable cochlea cannot benefit from a cochlear implant. The focus of the paper is to review the development and translation of a new type of central auditory prosthesis for this group of patients, which is known as the audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…These findings indicate an incomplete transition to average-rate coding of vowellike sounds in the IC and underscore the significance of temporal discharge patterns for perception of complex sounds. Furthermore, they highlight the potential benefits of incorporating F0-related envelope structure into stimulation strategies for auditory midbrain implants, which currently provide inadequate temporal information for robust speech perception (Lim and Lenarz 2015). Finally, model simulations showed that average-rate coding of vowel-like sounds in quiet emerges from a synchrony-based representation in more peripheral nuclei due to amplitude-modulation tuning.…”
Section: Discussionmentioning
confidence: 91%
“…These findings indicate an incomplete transition to average-rate coding of vowellike sounds in the IC and underscore the significance of temporal discharge patterns for perception of complex sounds. Furthermore, they highlight the potential benefits of incorporating F0-related envelope structure into stimulation strategies for auditory midbrain implants, which currently provide inadequate temporal information for robust speech perception (Lim and Lenarz 2015). Finally, model simulations showed that average-rate coding of vowel-like sounds in quiet emerges from a synchrony-based representation in more peripheral nuclei due to amplitude-modulation tuning.…”
Section: Discussionmentioning
confidence: 91%
“…This underlines the importance of further AMI development including electrode design, stimulation strategy, and surgical procedure. In the second clinical trial, efforts are now under way to improve hearing performance in patients implanted with an AMI by reducing the effective stimulation rate per channel and by increasing the number of available stimulation channels with a double‐shank electrode [Lim and Lenarz, ]. With further extensive development, the AMI may turn out to be a device with a great future potential, especially for patients that cannot benefit from a CI or ABI.…”
Section: Discussionmentioning
confidence: 99%
“…The variability and limitation in outcomes with central auditory implants may have different causes: Neural damage might emerge due to the surgery, the electrode array may be placed inaccurately [Colletti et al, ], or the growth of bilateral cochleovestibular schwannomas in patients with neurofibromatosis type 2 (NF2) may cause damage in the cochlear nucleus [Behr et al, ]. Moreover, central auditory implants do not yet have suitable electrode array designs and the used CI processing strategies are not optimized for stimulation of more centrally located nervous structures [Lim and Lenarz, ; McKay et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Ling et al (2015) review the conception and research of vestibular implants to treat balance-related disorders including disequilibrium, oscillopsia, or vertigo. Lim and Lenarz (2015) describe the development and translation of the auditory midbrain implant for patients without a functional auditory nerve or implantable cochlea. To overcome the intrinsic limitations related to broad electric stimulation, novel optogenetic stimulation has been proposed to demonstrate the proof of principle in developing an optical cochlear implant (Jeschke and Moser, 2015) and an optical auditory brainstem implant (Hight et al, 2015).…”
Section: Future Research In Cochlear Implantsmentioning
confidence: 99%